Idoso institucionalizado: repercussões da independência funcional - Brito, Flávia Fazani (2008)
The purpose of this study was that of investigating the repercussions of the physical independence in elderly people, residents in an institution of long permanence, the Recanto dos Velhinhos de Valinhos. I intend to find out the repercussions of the functional independence for the institutionalized elderly people. Fourteen physically independent elderly people were interviewed; all of them presented cognitive conditions to supply clear answers. The qualitative research started with a semi-structured itinerary, analyzing each witness's speeches in an individual way, and further on, those speeches were related in accordance with the thematic categories. Through data analysis, I aimed at investigating the possible repercussions of the functional independence, observing how that interferes in the institutionalized elderly people's life. The interviewees have demonstrated autonomy in the accomplishment of daily tasks, satisfaction as for the choices of the activities accomplished, sociability, and enthusiasm in being able of helping the companions and of practicing frequent physical activities